Psychodynamic Approach in Learning English at Junior High School - Aulia Rahmah; Muhammad Basri; Kisman Salija (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This research aimed to the students' learning components with the psychodynamic approach by identifying the students perceive the psychodynamic approach in learning English, how students implement the psychodynamic approach in learning English, and how students' implementation of the psychodynamic approach impacts the students' English learning achievement. This research occurred in SMP Negeri 3 Sungguminasa, Gowa, and employed qualitative research methods with the observation checklist and semi-structured interview instruments. The participants of the research are six students in the VIII grade. The result of the research concluded that the subconscious mind of students plays a fundamental role in shaping their attitudes toward learning. Student perceptions of learning English indicate that it is difficult, leading to two significant outcomes: motivation and a lack of self-efficacy. This perception also impacts their learning achievements, as the ineffective classroom learning process prevents students from mobilizing their mental energy to perform cognitive functions effectively.